Prospective Study of E?cacy of Intracu? Dexamethasone, Lignocaine and Normal Saline on Post Extubation Response - P. Rajeswar; Suresh Kumar Esampalli (Academia Anesthesiologica International, 2020)
Background: Post-surgical throat pain is the most common symptom after endotracheal intubation and is seen in up to 90 percent of patients. It can be considered along with the appearance of the endotracheal tube with laryngeal edema and ischemia. Chemical and mechanical tracheal mucosal inflammation affects the occurrence of cough from general anesthesia at the time of emergence, possibly leading to severe postoperative complications. During the emergence of a sore throat in a lighter plane of anesthesia, adverse hemodynamic changes can result. These changes are especially undesirable in patients undergoing neurosurgery, ophthalmic surgery or those with an increased risk of adverse cardiovascular incidents. The aims is to the purpose of this research is to determine and compare the effectiveness of intra-cuff dexamethasone and lignocaine in reducing the adverse effects of the post-extubation airway as a control group with normal saline. Subjects and Methods: Prospective study was performed on 90 patients admitted to general anaesthesia for separate operations. After having received approval from the institutional ethics committee and written informed consent, they were randomly divided into 3 groups of 30 patients each. Results: Among the three classes of surgical, anaesthetic, and baseline characteristics, there were no statistically significant differences. In terms of cough, the three groups differed significantly (p = 0.02). In other words, while lignocaine was more beneficial for the occurrence of cough after extubation, dexamethasone affected the severity of post-extubation cough more than the other 2 medications. In comparison with the dexamethasone and standard saline groups, spontaneous ventilation time and time to extubation (increase in endotracheal tolerance) were also extended in the lignocaine community. The three classes did not vary substantially in terms of patient satisfaction after 24 hours. Conclusions: When Dexamethasone is inflated with the endotracheal tube cuff, the incidence of postoperative sore throat and cough, but not speech hoarseness, is decreased.